The role of childhood health for the intergenerational transmission of human capital: evidence from administrative data - Martin Salm; Daniel Schunk (Institute for the Study of Labor (IZA), 2008)
We use unique administrative German data to examine the role of childhood health for the intergenerational transmission of human capital. Specifically, we examine the extent to which a comprehensive list of health conditions - diagnosed by government physicians - can account for developmental gaps between the children of college educated parents and those of less educated parents. In total, health conditions explain 18% of the gap in cognitive ability and 65% of that in language ability, based on estimations with sibling fixed effects. Thus, policies aimed at reducing disparities in child achievement should also focus on improving the health of disadvantaged children.
urn:nbn:de:101:1-20080825237
Keywords: J13; 330; Health inequality; human capital formation; childhood health; intergenerational mobility; Kinder; Gesundheit; Bildungsinvestition; Bildungsniveau; Generationenbeziehungen; Familiensoziologie; Deutschland